2012
DOI: 10.3340/jkns.2012.52.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Calcium on Spinal Bone Fusion in an Ovariectomized Rat Model

Abstract: ObjectiveTo evaluate the effect of calcium supplementation on spinal bone fusion in ovariectomized (OVX) rats.MethodsSixteen female Sprague Dawley rats underwent bilateral ovariectomy at 12 weeks of age to induce osteoporosis and were randomly assigned to two groups : control group (n=8) and calcium-supplemented group (OVX-Ca, n=8). Autologous spinal bone fusion surgery was performed on both groups 8 weeks later. After fusion surgery, the OVX-Ca group was supplemented with calcium in drinking water for 8 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…This method of administration was used in our previous study [36] and has also been used by others [37]. The advantage of using this route of administration is that it minimizes the stress from using injection or oral gavage.…”
Section: Discussionmentioning
confidence: 99%
“…This method of administration was used in our previous study [36] and has also been used by others [37]. The advantage of using this route of administration is that it minimizes the stress from using injection or oral gavage.…”
Section: Discussionmentioning
confidence: 99%
“…Bone morphometric parameters and microarchitectural properties were analyzed by microcomputed tomography (μCT) of the left femur using a Skyscan 1172 micro‐CT scanner (Kontich, Belgium). The scanning protocol was followed to the previous study [Cho et al, ]. The bone mineral density (BMD), trabecular number (Tb.N), bone volume/total volume ratio (BV/TV), trabecular thickness (Tb.Th), trabecular pattern factor (Tb.Pf), and structure model index (SMI) were used to produce quantitative data in the Skyscan NRecon program and analyzed using Skyscan CTAN software.…”
Section: Methodsmentioning
confidence: 99%
“…However, the risks of calcium supplementation are low, with 1 large RCT reporting 92 000 adverse events, of which only constipation was increased by calcium supplementation. 22 Although an animal-model study demonstrated that rats receiving dietary calcium supplements had improved lumbar fusions, 23 there have been no clinical studies to support this in spine surgery patients. Vitamin D, as well, is an important factor in bone formation and maintenance.…”
Section: Calcium and Vitamin Dmentioning
confidence: 96%